Phytochemical and toxicological evaluation of Zephyranthes citrina - Rehman, Muhammad Haseeb Ur; Saleem, Uzma; Ahmad, Bashir; Rashid, Memoona (Frontiers in Pharmacology, 2022)
Drugs obtained from medicinal plants have always played a pivotal role in the field of medicine and to identify novel compounds. Safety profiling of plant extracts is of utmost importance during the discovery of new biologically active compounds and the determination of their efficacy. It is imperative to conduct toxicity studies before exploring the pharmacological properties and perspectives of any plant. The present work aims to provide a detailed insight into the phytochemical and toxicological profiling of methanolic extract of Zephyranthes citrina (MEZ). Guidelines to perform subacute toxicity study (407) and acute toxicity study (425) provided by the organization of economic cooperation and development (OECD) were followed. A single orally administered dose of 2000 mg/kg to albino mice was used for acute oral toxicity testing. In the subacute toxicity study, MEZ in doses of 100, 200, and 400 mg/kg was administered orally, consecutive for 28 days. Results of each parameter were compared to the control group. In both studies, the weight of animals and their selected organs showed consistency with that of the control group. No major toxicity or organ damage was recorded except for some minor alterations in a few parameters such as in the acute study, leukocyte count was increased and decreased platelet count, while in the subacute study platelet count increased in all doses. In the acute toxicity profile liver enzymes Alanine aminotransferase (ALT), as well as, aspartate aminotransferase (AST) were found to be slightly raised while alkaline phosphatase (ALP) was decreased. In subacute toxicity profiling, AST and ALT were not affected by any dose while ALP was decreased only at doses of 200 and 400 mg/kg. Uric acid was raised at a dose of 100 mg/kg. In acute toxicity, at 2000 mg/kg, creatinine and uric acid increased while urea levels decreased. Therefore, it is concluded that the LD50 of MEZ is more than 2000 mg/kg and the toxicity profile of MEZ was generally found to be safe.